Corrosion fatigue failure of a high carbon CoCrMo modular hip prosthesis: Failure analysis and electrochemical study. (November 2019) - Lanzutti, A.; Andreatta, F.; Rossi, L.; Di Benedetto, P.; Causero, A.; Magnan, M.; Fedrizzi, L.
Abstract: The use of CoCr alloys, to produce necks for modular prosthesis, is well known in the field of orthopaedics, in particular in modular hip prosthesis subjected to high fatigue loads. The work presents an unexpected fatigue related in-vivo failure of a high carbon CoCrMo alloy, used to produce the neck of a modular hip prosthesis. The first part of the work is focused on the characterization of the failed component by means of SEM analysis of the fractured prosthesis. The second part of the work focuses on the electrochemical (Electrochemical Potentiokinetic Reactivation curves) and microstructural characterization (SEM, light microscope and Scanning Kelvin Probe Force Microscopy) of both high and low carbon CoCrMo alloys, in order to determine the possible in-vivo degradation that could locally decrease the fatigue properties of the material. The results showed that the prosthesis failure was promoted by a kind of selective corrosion, occurring at a narrow crevice generated by the mechanical joint between the Ti alloy stem and the CoCrMo alloy neck. The selective corrosion worked as stress raiser favouring fatigue cracks nucleation, then locally reducing the fatigue resistance of the component. Moreover, it was observed that the high carbon CoCrMo alloy is susceptible to a local selective dissolution of the metal matrix close to the CrMo primary carbides, that behave as local cathodes, promoting an intergranular like selective corrosion. On the other hand, a similar degradation is not visible in the low carbon CoCrMo alloy. Highlights: A failure analysis of a modular hip prosthesis was performed. Intergranular selective corrosion morphology was observed in the CoCrMo alloy neck, at the joint interface. Cr-Co primary carbides favored the selective dissolution of the matrix acting as local cathodes. The selective corrosion worked as local stress raiser favouring fatigue cracks nucleation. The mechanism of failure was corrosion-fatigue.